Multi-functional mesoporous β-Ga2O3: Cr3+ nanorod with long lasting near infrared luminescence for in vivo imaging and drug delivery1. Issue 17 (27th February 2015) - Wang, Xin-Shi; Li, Wei-Shuo; Situ, Jun-Qing; Ying, Xiao-Ying; Chen, Hui; Jin, Yi; Du, Yong-Zhong
<x xml:space="preserve">Abstract</x> β-Ga2O3: Cr3+ nanorod can maintain its near infrared signal after the removal of the exciting UV, and this afterglow can be acquired by a CCD camera without an external light source.